Implementasi Algoritma Pencarian Rute Dijkstra Pada Game Great Elephant dengan Unity Engine - Ahmad Zuhdi; Ryan Aji Wijaya; M. Abu Jihad Plaza R; Nadia Salsabila (LPPM Universitas Muhammadiyah Kotabumi, 2026)
The rapid development of modern game technology drives the urgent need for efficient pathfinding systems and structured development processes. In maze-based games, routing algorithms are highly crucial for regulating Non-Player Character (NPC) movements optimally. This research implements the Dijkstra algorithm for shortest pathfinding on an elephant character in the 2D game